Cultural Authenticity and Recovery Maintenance in a Rural First Nation Community - Nygaard, Aimee (International Journal of Mental Health and Addiction, 2011)
This study explored a rural, First Nation understanding of factors, particularly the role of culture, supporting recovery maintenance from problem substance use. A cross- sectional, qualitative research design and community-based methodology were used. Participants included 20 members of a rural Canadian community self-identifying as recovering, or recovered, problem substance users, and those with professional experience with First Nations recovery. Semi-structured, open-ended interviews gathered in-depth accounts of the recovery experience examined through a thematic analysis. Culture emerged as a contested concept, and was viewed along a spectrum from detrimental, to somewhat helpful to very beneficial in the recovery process. Community change emerged as a key theme. Conclusions suggest that the tension in understandings of culture in this context inhibit potential social supports for recovery. However, whatever power culture may hold, socio-economic context is also a significant factor that must be addressed to support long term recovery.